Infertility, Adoption and Metaphorical Pregnancies: 2013 Award Winner for Student Paper in Feminist Anthropology - Lockerbie, Stacy (Anthropologica, 2014)
In this article, I explore the grief some women experience as a result of their inability to have children or, what Linda Layne (1996:132) has called, "a loss of innocence," the loss of the taken-for-granted assumption that being a woman means that you can bear children. This innocence lost is connected to their shattered faith in medical progress, and the disruption of profoundly held beliefs about the nature of womanhood. Here, I elucidate how these women anchor the adoption experience in pregnancy by using pregnancy metaphors to describe the adoption process whereby adopted children are said to grow in a woman's heart instead of her womb.